2017
DOI: 10.1002/jbm.a.36111
|View full text |Cite
|
Sign up to set email alerts
|

5‐Azacytidine‐mediated hMSC behavior on electrospun scaffolds for skeletal muscle regeneration

Abstract: Incomplete regeneration after trauma or muscular dysfunction is a common problem in muscle replacement therapies. Recent approaches in tissue engineering allow for the replication of skeletal muscle structure and function in vitro and in vivo by molecular therapies and implantable scaffolds which properly address muscle cells toward myotube differentiation and maturation. Here, we investigate the in vitro response of human mesenchymal stem cells (hMSC) on electrospun fibers made of polycaprolactone (PCL) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
(43 reference statements)
1
20
0
Order By: Relevance
“…Muscle defects and degenerative diseases affect the lives and quality of life of many patients worldwide.The administration of the drug is ine cient at regenerating damaged tissue, and the toxicity of the drug is a major blow to the patient's body.Stem cell therapy is considered a good way to repair lost cells [12].Mesenchymal stem cells (MSCs) have the ability of self-renewal, multidirectional differentiation and immune regulation, and they are the most ideal candidate cells in cell therapy and regenerative medicine [12]. MSCs are derived from many tissues including bone marrow [16], lung [17], fat [18], liver [19], umbilical cord [20], amniotic uid [21], placenta [22]and umbilical cord blood [23].It has been reported that these cells have the potential to differentiate into skeletal muscle [24], cardiomyocytes [25] and smooth muscle cells [26].Among cells of various sources, ADSCs are stem cells that have been repeatedly reported and clearly possess myogenic differentiation potential, and can differentiate into muscle tissue under the action of various induction products such as 5-aza, boron and cyclic uniaxial stress [27].Among the several products studied, 5-aza has been shown to be a suitable inducer with stable inductivity, despite the wide variety of products studied.5-aza is a cytidine like DNA methylation inhibitor which was known to promote up-regulation of muscle genes and differentiation of hMSC [27].Previous studies have shown that it can alter cell fate and differentiate MSCs into cardiomyocytes through a speci c molecular mechanism involving DNA demethylation and histone a key step in cell epigenetic modi cation [28]. However, due to the toxic effect of 5-aza, cell viability is limited and myoblast differentiation e ciency is not high.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle defects and degenerative diseases affect the lives and quality of life of many patients worldwide.The administration of the drug is ine cient at regenerating damaged tissue, and the toxicity of the drug is a major blow to the patient's body.Stem cell therapy is considered a good way to repair lost cells [12].Mesenchymal stem cells (MSCs) have the ability of self-renewal, multidirectional differentiation and immune regulation, and they are the most ideal candidate cells in cell therapy and regenerative medicine [12]. MSCs are derived from many tissues including bone marrow [16], lung [17], fat [18], liver [19], umbilical cord [20], amniotic uid [21], placenta [22]and umbilical cord blood [23].It has been reported that these cells have the potential to differentiate into skeletal muscle [24], cardiomyocytes [25] and smooth muscle cells [26].Among cells of various sources, ADSCs are stem cells that have been repeatedly reported and clearly possess myogenic differentiation potential, and can differentiate into muscle tissue under the action of various induction products such as 5-aza, boron and cyclic uniaxial stress [27].Among the several products studied, 5-aza has been shown to be a suitable inducer with stable inductivity, despite the wide variety of products studied.5-aza is a cytidine like DNA methylation inhibitor which was known to promote up-regulation of muscle genes and differentiation of hMSC [27].Previous studies have shown that it can alter cell fate and differentiate MSCs into cardiomyocytes through a speci c molecular mechanism involving DNA demethylation and histone a key step in cell epigenetic modi cation [28]. However, due to the toxic effect of 5-aza, cell viability is limited and myoblast differentiation e ciency is not high.…”
Section: Discussionmentioning
confidence: 99%
“…Konigsberg long pointed out the importance of the extracellular matrix (ECM) protein collagen as a critical component to the development of muscle colonies, which led to its widespread use in SMTE . Since then, other natural and synthetic materials such as fibrin, alginate, polycaprolactone (PCL)‐based polymers, and various strategies have been developed to generate skeletal muscle tissues in vitro. Especially, the engineering of muscle fibers in vitro requires the culture of myoblasts in an anisotropic environment, promoting their alignment, favoring their fusion and the myogenesis .…”
Section: Skeletal Muscle Tissue Engineeringmentioning
confidence: 99%
“…Different in vitro techniques such as soft lithography 18 , laser texturing 19 , electrospinning 20 , and electrospraying 21 , have been employed to generate 2D cell-laden constructs. However, these techniques fail to accurately mimic the mechanical properties, architecture and physiology of brain-speci c structure and function 22 .…”
Section: Introductionmentioning
confidence: 99%